Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012 6th International Conference on Signal Processing and Communication Systems 2012
DOI: 10.1109/icspcs.2012.6507959
|View full text |Cite
|
Sign up to set email alerts
|

Scheme for enhanced tracking of mobile subscribers in a WiMAX network

Abstract: In this paper, the base station identification and timing adjust measurements are used to geolocate mobile subscribers in a WiMAX network. The uplink and downlink subframes of the physical layer and management messages of the medium access control layer are examined to extract the necessary data for geolocation. Using a hidden Markov model [1] based algorithm to estimate the track of the mobile subscriber, we demonstrate that the position error can be further reduced by incorporating timing adjust measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…As our study focuses on network deployment using modern 4G standards, we find it convenient to exploit the built in TA in conjunction with associated base station IDs (BSID) to this end. Simulation has shown that TA data can dramatically improve accuracy when such data are available (Henderson, 2011;Henderson et al, 2012). When it is not available, or if it is not available at a sufficiently frequent interval, the proposed HMM-augmented fingerprinting method described in the preceding section can be used unassisted.…”
Section: Refinement By Timing Adjustmentioning
confidence: 96%
See 4 more Smart Citations
“…As our study focuses on network deployment using modern 4G standards, we find it convenient to exploit the built in TA in conjunction with associated base station IDs (BSID) to this end. Simulation has shown that TA data can dramatically improve accuracy when such data are available (Henderson, 2011;Henderson et al, 2012). When it is not available, or if it is not available at a sufficiently frequent interval, the proposed HMM-augmented fingerprinting method described in the preceding section can be used unassisted.…”
Section: Refinement By Timing Adjustmentioning
confidence: 96%
“…Scalability is the central theme of our contribution enabling significant reduction in computational cost. Additionally, where other fingerprinting localisation schemes typically use only a two-phase program (offline database training and online localisation) (Bshara et al, 2011;Henderson et al, 2012;Malik & Allen, 2006;Nypan et al, 2002;Roxin et al, 2007;Xu & Jiang, 2012), our proposed scheme uses three phases: an offline database training phase, an online International Journal of Systems Science 3 localisation phase, and optional HMM and TA augmentation. Our technique of TA integration furthers our ability to scale the data without compromising accuracy.…”
Section: Hmm-assisted Fingerprint-based Localisation Schemementioning
confidence: 99%
See 3 more Smart Citations